Pengaruh Budaya Organisasi dan Motivasi Kerja terhadap Kinerja Karyawan PT XYZ di Kabupaten Bekasi - Agustin, Fadia Etwina Nur; Sukoco, Iwan; Dai, Ratna Meisa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Employee performance is a strategic factor in achieving organizational goals, particularly in the manufacturing sector which demands high efficiency. PT XYZ faces challenges in maintaining employee performance amid changes in the work environment. This study aims to analyze the influence of organizational culture and work motivation on employee performance. A quantitative approach was used by conducting a survey of all 62 permanent employees through a Likert scale questionnaire. Data were analyzed using multiple linear regression with SPSS version 29. The results show that both organizational culture and work motivation significantly affect employee performance, both individually and jointly. The Adjusted R² value of 0.679 indicates that 67.9% of the variation in performance can be explained by these two variables. The organizational culture, which incorporates Japanese principles such as Kaizen and 5R, helps create a structured and collaborative work environment, although the implementation is not uniform across divisions. Meanwhile, work motivation, especially the need for achievement, has a more dominant impact on performance. These findings emphasize that the combination of a strong organizational culture and an inclusive motivation system is a key foundation in developing human resource competitiveness in multinational companies.